Implementation of the Independent Curriculum through Project for Strengthening Pancasila Student Profilesto FKIP PBSI Al Washliyah Muslim University Medan Students - Fatria, Fita; Husna, Tiflatul; Purba, Alfitriana (Westscience Press, 2024)
This research aims to implement the Independent Curriculum through the Project for Strengthening the Profile of Pancasila (P5) Students Based on Character Education for FKIP PBSI Students at Al Washliyah Muslim Nusantara University, Medan. Bearing in mind that student character formation must be improved through the P5 independent curriculum program. The project to strengthen the Pancasila student profile, as a means of achieving the Pancasila student profile, provides students with the opportunity to